The Shift in the Behavior of Methylene Blue Toward the Sensitivity of Medium: Solvatochromism, Solvent Parameters, Regression Analysis and Investigation of Cosolvent on the Acidity Constants - Hemdan, Sokaina Saad (Journal of fluorescence, 2023)
The influence solvents from different polarity and hydrogen bonding ability on electronic absorption spectrum of Methylene blue was investigated. The visible absorption spectra were recorded in eleven neat solvents in the range 400–700 nm. Methylene blue has two absorption maxima, the first band assigned to n-π* from amino groups and the second band assigned to weakly forbidden n-π* transition with charge transfer. The charge transfer band of Methylene blue showed red shift with increasing the relative permittivity of neat solvents. The red shift in wavelength(λ max ) for the charge transfer band of Methylene blue was observed when proceeding from dioxane (λ max = 650 nm) into methanol (λ max = 655 nm) into cyclohexanone (λ max = 660 nm) into dimethylsulfoxide (λ max = 665 nm) as well as water (λ max = 665 nm), this shift not agree with the polarity of solvents but due to combination of several parameters. The absorption of charge transfer band in methanol and ethanol as hydrogen bonding donating solvents (HBD) showed the highest intensity than the absorption band in dimethylsulfoxide and dimethylformamide as hydrogen bonding accepting solvents (HBA) due to non-electrostatic interaction between the amino groups and solvents. The charge transfer band in neat solvents were correlated with several parameters using linear solvation energy relationships. The results showed that electrostatic interactions of the solvents play an important role in the shift of absorption maxima of Methylene blue in neat solvents. The acidity constants (pKa) of Methylene blue were estimated by using absorbance measurements in different media. The acidity constants (pKa) values of Methylene blue were affected by cosolvent, which the pKa values increasing in the order propanol < methanol < dioxane, this order not agreement with increasing the relative permittivity of the medium.